Effector memory T cells are associated with atherosclerosis in humans and animal models - Ammirati, E.; Cianflone, D.; Vecchio, V.; Banfi, M.; Vermi, A.; De Metrio, M.; Grigore, L.; Pellegatta, F.; Pirillo, A.; Garlaschelli, K.; Manfredi, A.; Catapano, A.; et al. (Wiley-Blackwell, 2012)
Background- Adaptive T-cell response is promoted during atherogenesis and results in the differentiation of näive CD4 + T cells to effector and/or memory cells of specialized T-cell subsets. Aim of this work was to investigate the relationship between circulating CD4 + T-cell subsets and atherosclerosis. Methods and Results- We analyzed 57 subsets of circulating CD4+T cells by 10-parameter/8-color polychromatic flow cytometry (markers: CD3/CD4/CD45RO/CD45RA/CCR7/CCR5/CXCR3/HLA-DR) in peripheral blood from 313 subjects derived from 2 independent cohorts. In the first cohort of subjects from a free-living population (n=183), effector memory T cells (T EM : CD3 + CD4 + CD45RA - CD45RO + CCR7- cells) were strongly related with intima-media thickness of the common carotid artery, even after adjustment for age (r=0.27; P < 0.001). Of note, a significant correlation between T EM and low-density lipoproteins was observed. In the second cohort (n=130), T EM levels were significantly increased in patients with chronic stable angina or acute myocardial infarction compared with controls. HLA-DR+T EM were the T EM subpopulation with the strongest association with the atherosclerotic process (r=0.37; P < 0.01). Finally, in animal models of atherosclerosis, T EM (identified as CD4 + CD44 + CD62L - ) were significantly increased in low-density lipoprotein receptor and apolipoprotein E deficient mice compared with controls and were correlated with the extent of atherosclerotic lesions in the aortic root (r=0.56; P < 0.01). Conclusions- Circulating T EM cells are associated with increased atherosclerosis and coronary artery disease in humans and in animal models and could represent a key CD4 + T-cell subset related to the atherosclerotic process. © 2012. The Authors.